Yunniarsih, Riris DAMPAK PENGENDALIAN OPERASINAL HOUSEKEEPING DEPARTMENT GUNA MENINGKATKAN EFISIENSI COST DI WETA INTERNATIONAL HOTEL SURABAYA (JBT (JURNAL BISNIS dan TEKNOLOGI), 2014)
Housekeeping department is a department that has the duty and responsibility in the cleanliness of the hotel area. In order to guarantee the smooth operation of the housekeeping department requires very high costs, therefore the Executive Housekeeper should perform operational control housekeeping activities so as to reduce the burden of these costs. The purpose of this study was to describe the role of maid of operational control in order to improve the cost efficiency of the company. The analysis used to achieve that goal is a qualitative descriptive analysis. The study was conducted in the Housekeeping department Weta International Hotel Surabaya. The results showed that after controlling operational activities, production costs to be incurred can be suppressed well, without reducing the quality of the products produced and the productivity of employees at work.